Visual Assessment pada Bangunan Gedung Terhadap Sistem Keamanan Kebakaran - Fanny Monika; Siti Solihah; Hakas Prayuda; Lilis Tiyani; Bella Lutfiani Al Zakina (Bulletin of Civil Engineering, 2022)
Fire is a hazard caused by an uncontrollable flame, resulting in both material and moral losses. Fire problem occurs when firefighting equipment is often ignored during the construction planning of a building, for that we need to check and supervision the fire safety system in multilevel buildings. The purpose of this research is to determine the level of reliability of building fire safety system in Forriz Hotel Yogyakarta and is expected to be a refence fire protection system in other commercial buildings in Yogyakarta. this research used a method by direct observation on fire protection system with reference to fire safety inspection guidelines for building (Pd-T-11-2005-C). The result of this research is reliability value of building safety for each component consisting of the value of completeness of the site of 22,7% (less), means of the rescue of 16,4% (less), active protection of 15,1% (less), passive protection of 24,3 (less). The calculation results for the reliability of the building of Hotel Forriz Yogyakarta is 78,5% or in the Enough category. Based on the research result Hotel Forriz Yogyakarta cannot be used for reference to the implementation of the fire protection system in buildings.Â